Legal Analysis of Communal Rights in Copyright Protection: Challenges and Reform Proposals in Indonesia - Hafaiz, Muhammad Rizkya (Law and Economics, 2024)
This research provides a legal analysis of communal rights in copyright protection within the. Indonesian legal framework, focusing on the challenges faced by indigenous and local communities in safeguarding their traditional cultural expressions and knowledge. The study reveals that Indonesia's Copyright Act No. 28 of 2014 predominantly emphasizes individual authorship, offering limited protection for communal intellectual property. Through a comparative analysis of international best practices and case studies from jurisdictions such as Australia and Canada, the research underscores the inadequacies of current laws in addressing collective ownership. Key findings indicate that the lack of legal recognition for communal rights, coupled with weak enforcement mechanisms, leaves traditional knowledge and cultural heritage vulnerable to exploitation. The research highlights the need for comprehensive legal reforms that explicitly protect communal intellectual property, enhance enforcement, and ensure community participation in the legal process. Recommendations include amending the copyright law to incorporate communal ownership provisions, developing policies that promote community engagement, and aligning Indonesia’s legal framework with international intellectual property standards. This study contributes to the broader discourse on intellectual property law by proposing actionable solutions to bridge the gap between individual rights and communal interests, ultimately aiming to protect Indonesia’s cultural heritage in a more equitable and effective manner.